Current Strategies and Future Prospects of Achondroplasia Treatment : A Systemic Review - Bednarczyk, Daria; Pysiewicz, Wiktoria; Garbarczyk, Wiktor; Napieralska, Agnieszka; Kapla, Albert; Jurkiewicz, Michalina; Białeta, Julia; Rowińska, Katarzyna; Siembab, Karolina; Černohorská, Alicja (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: Achondroplasia, the most common form of dwarfism, results from mutations in the FGFR3 gene. The disorder causes disproportionate short stature due to a gain-of-function mutation in FGFR3, impacting bone growth. Patients often face various health challenges, including orthopedic, neurological, and respiratory issues. This review aims to analyze current treatment strategies, their limitations, and highlight promising new approaches for managing achondroplasia. Materials and Methods: This review synthesizes available literature on the clinical management of achondroplasia, focusing on treatment modalities such as growth hormone therapy, limb lengthening techniques, spinal surgery, and gene therapies. Emphasis is placed on understanding the efficacy, challenges, and emerging therapies for this genetic condition. Results: Current treatment approaches include recombinant human growth hormone (rhGH) therapy, which has shown modest success in increasing height but has limited long-term benefits. Limb lengthening remains a cornerstone for improving quality of life, with techniques like the Ilizarov method and PRECICE system, though complications and high costs persist. Spinal surgeries for foramen magnum stenosis and kyphosis provide relief but are complex and require individualized care. New treatments like Vosoritide, a CNP analogue, show promise by promoting bone growth. Gene-editing techniques like CRISPR/Cas9 offer potential for correcting the underlying genetic mutations. Conclusion: Achondroplasia management continues to evolve with a combination of surgical, pharmacological, and genetic interventions. While limb lengthening and spinal surgeries significantly improve quality of life, new treatments like Vosoritide and CRISPR/Cas9 may revolutionize care by addressing the root cause of the condition. Ongoing research and clinical trials will likely refine these approaches, offering better outcomes for patients with achondroplasia.